Global readiness for carbon neutrality: From targets to action - Shihui Zhang; Wenjia Cai; Xinzhu Zheng; Xuedu Lv; Kangxin An; Yuan Cao; Hou Sang Cheng; Jingyi Dai; Xinyang Dong; Shuting Fan; Yiying Gao; Zaizuo Gong; et al. (Environmental Science and Ecotechnology)
The global push for carbon neutrality highlights the need for rigorous assessments of whether national efforts align with stated targets. However, existing evaluations often prioritize commitments over tangible progress, lacking comprehensive and transparent metrics. To bridge this gap, we develop a multidimensional indicator system that evaluates targets, policies, actions, and effectiveness across key areas, including policy implementation, technology deployment, financial investment, and international cooperation. While 151 countries have pledged carbon neutrality—19 of which are developing nations that made commitments in 2024—implementation remains uneven. Only 72 countries have established complete policy frameworks, and advanced low-carbon technologies are concentrated in a handful of nations. Current trends indicate that global renewable energy capacity will reach just 2.7 times its 2022 level by 2030, falling short of the tripling target. Moreover, the global median action score in 2024 stands at only 25—far below the target of 65—highlighting the urgency for stronger efforts. Our findings reveal a significant gap between ambition and action, with renewable energy deployment lagging behind expectations. To accelerate progress, enhanced global cooperation, increased investment, and fewer barriers to technology diffusion are crucial. This study underscores the need for more implementation-focused tracking to ensure carbon neutrality commitments translate into measurable outcomes.